The frequency of sarcopenia in the post-COVID period and its relationship with the clinical course of the COVID-19 (Annals of Medical Research, 2022)
Aim: We designed this study with the intention of determining the prevalence of sarcopenia and the association between sarcopenia findings and the severity of COVID-19 disease in COVID-19 patients. Materials and Methods: As the study group, 92 patients aged 50 and over years old and whose PCR test results were positive and 45 days passed after the test result and recovered, 92 healthy individuals over 50 years of age, who were not infected with COVID-19 , were included in the study group.Results: While 33.7% of the patient group had severe sarcopenia, 7.61% sarcopenia, 30.43% probable sarcopenia, 28.26% did not have sarcopenia. While 3.26% severe sarcopenia and 10.87% probable sarcopenia were observed in the control group, 85.87% sarcopenia was not observed. The incidence of sarcopenia in the patient group was significantly higher than in the control group (p
Keywords: COVID-19; Muscle pain; Sarcopenia